Developing and testing a framework to measure and monitor safety in healthcare. (May 2014) - Illingworth, John
The NHS excels at measuring incidences of past harm – whether it is falls or hospital-acquired infections – but research undertaken by Charles Vincent, Jane Carthey and Susan Burnett for the Health Foundation suggests past harm is only one element of what is needed to understand how safe care is. The researchers developed a framework to incorporate other necessary elements, such as anticipating and preparing for risks before they lead to harm to patients. In 2013, the Health Foundation road-tested this framework with staff in three NHS organisations and held a two-day summit with leaders from across the healthcare system to get feedback on its potential. This article presents the findings of this phase of work and sets it in the context of recent changes in the policy and regulatory landscape for patient safety in England. It concludes that the framework offers a great deal of potential for supporting organisations to understand the safety of their services. The framework could be most effective when used to identify the relative strengths and weaknesses of current safety measures, and when staff are given sufficient time, resource and support to consider the complex issues surfaced by the questions in the framework. This needs to be matched by a system of regulation which is aligned and mature, and an approach from NHS Trust Boards which welcomes information about the risks of its services.